Protein-mediated looping of DNA under tension requires supercoiling. Issue 5 (22nd January 2018) - Yan, Yan; Leng, Fenfei; Finzi, Laura; Dunlap, David
Abstract: Protein-mediated DNA looping is ubiquitous in chromatin organization and gene regulation, but to what extent supercoiling or nucleoid associated proteins promote looping is poorly understood. Using the lac repressor (LacI), a paradigmatic loop-mediating protein, we measured LacI-induced looping as a function of either supercoiling or the concentration of the HU protein, an abundant nucleoid protein in Escherichia coli . Negative supercoiling to physiological levels with magnetic tweezers easily drove the looping probability from 0 to 100% in single DNA molecules under slight tension that likely exists in vivo . In contrast, even saturating (micromolar) concentrations of HU could not raise the looping probability above 30% in similarly stretched DNA or 80% in DNA without tension. Negative supercoiling is required to induce significant looping of DNA under any appreciable tension.